2020
DOI: 10.1530/rep-19-0340
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of epigenetic inheritance of variable traits through the germline

Abstract: During the past half century, evidence for inheritance of variable traits has accumulated from experiments in plants and animals and epidemiological studies in humans. Here, we summarize some of the reported cases of epigenetic inheritance and the proposed mechanisms involved in the transmission of non-genetic information between generations in plants, nematodes, flies and mammals. It has long been accepted that information is epigenetically inherited in plants. Although many questions regarding the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 124 publications
0
15
0
Order By: Relevance
“…The alternative to a maternally mediated effect is a more direct effect by sires, through small RNAs or proteins deposited in the sperm cytoplasm, or through epigenetic modifications of the DNA transferred to offspring. Since D. melanogaster lacks methylation and there is no evidence as yet for paternal effects mediated by sperm loaded with small RNAs or proteins in this species [56], this leaves the possibility that the effect we observe is caused by remodelled chromatin. A previous study has indeed shown that diet-induced changes in chromatin state can affect lifespan in Drosophila [57].…”
Section: Discussionmentioning
confidence: 99%
“…The alternative to a maternally mediated effect is a more direct effect by sires, through small RNAs or proteins deposited in the sperm cytoplasm, or through epigenetic modifications of the DNA transferred to offspring. Since D. melanogaster lacks methylation and there is no evidence as yet for paternal effects mediated by sperm loaded with small RNAs or proteins in this species [56], this leaves the possibility that the effect we observe is caused by remodelled chromatin. A previous study has indeed shown that diet-induced changes in chromatin state can affect lifespan in Drosophila [57].…”
Section: Discussionmentioning
confidence: 99%
“…There were individuals across families in this study who expressed LEH in later generations, when LEH prevalence was generally low (perhaps due to favorable environmental conditions e.g., high food availability, relative economic affluence, low rates of infectious disease). The mechanisms for intergenerational transmission of stress, frailty, and susceptibility to disease (e.g., intrauterine environment, alterations to gamete and DNA methylation see Bowers & Yehuda, 2016;Vågerö et al, 2018;Casas & Vavouri, 2020), are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a mutual interaction between genetic background and epigenetic pathways has been suggested, resulting in a sophisticate modulation of cellular phenotype. Specifically, genetic changes may drive epigeneticsin particular SNPs controlling methylation levels at crucial CpG sites, as reported in several studiesand epigenetics may in turn regulate allele-specific expression of a particular risk variant [15,16].…”
Section: Genetic Versus Epigeneticmentioning
confidence: 97%